Absenteeism of public workers: short review - Edison Sampaio (2019)
Absenteeism can be defined as an absence of the worker to his work, regardless of the reasons. The objective of this work was to identify the most relevant reasons for public employees absenteeism, through a review of the scientific literature published in the last 5 years. The results pointed out that absenteeism could be associated with several types of indicators. Physical and psychic disorders are very relevant causes, but issues such as organisational justice, stress-reward balance, and demand control, as well as individual employee characteristics and contextual issues, have been strongly correlated with this problem. (c) Springer Nature Switzerland AG 2019.